Kinerja Keuangan Ditinjau Dari Likuiditas, Solvabilitas Dan Profitabilitas Pada Perusahaan Bumn Sektor Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2011-2024 - Navika Nur Mawaddah; Ida Aryati Dyah Purnomo Wulan; Ratna Damayanti (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the influence of liquidity, solvency, and profitability on the financial performance of state-owned banking companies listed on the Indonesia Stock Exchange (IDX for the period 2011 2024. This study uses a quantitative approach with descriptive methods. The data used are secondary data in the form of annual financial reports of companies and the Indonesia Stock Exchange, with a sample of 42 observations from twee state-owned banks. Data analysis uses multiple linear regression preceded by classical assumption tests, hypothesis testa, and coefficients of determination using the SPSS program. The results show that liquidity has a negative and insignificant effect on financial performance Meanwhile, solvency and profitability have a positive and significant effect on the financial performance of state-owned banking companies.